Metastases of squamous cell carcinoma in the lymph nodes of the neck without the revealed primary focus - I. G. Komarov; D. A. Karseladze; A. I. Senderovich; A. I. Karseladze; K. V. Smirnova; M. A. Кrylovetskaya (Опухоли головы и шеи)
Objective is to identify regularity of metastases distribution of the squamous cell carcinoma (SCC) in the lymph nodes of the neck without revealed primary focus, as well as to evaluate the effectiveness of various methods of treatment.Materials and methods. Performed the retrospective 45 patients data analysis with metastases of SCC in cervical lymph nodes without  the revealed primary focus treated in different departments of N.N. Blokhin National Medical Research Center of Oncology from 2005  to 2012. The source of information were outpatient studies and medical histories, histological preparations and paraffin blocks.Results. Metastases of SCC without revealed primary focus are most typical for nodes of a neck and upper part of the body, there are among the patients mostly males aged 50–59 years. To establish the localization of the primary focus, traditional diagnostic procedures are not always effective: in morphological analysis, the primary focus can be hidden behind inflammatory changes, in addition, the tumor lesion can be of a primary focus. Tumors, similar to lymphoepithelioma-like carcinoma, could also simulate metastasis in the lymph node. Tonsil cancer is very often not detected even with repeated biopsies, therefore diagnostic tonsillectomy is justified. Survival depends slightly  on the identification of the source of metastasis. The range of treatment methods for SCC is limited, combined and complex methods demonstrate greater efficiency, chemotherapy is less reasonable. The leading prognostic factor is the degree of distribution of metastatic lesion. Virologic analysis allows only to assume localization of the tumor process in the nasopharynx in patients with human papillomavirus and predict their greater survival, and the number of patients with Epstein–Barr virus is too small for reasonable hypotheses.Conclusion. With metastases of SCC in the lymph nodes of the neck without the revealed primary focus, the hidden distributing tumor is most often appears in the pharyngeal tonsils and in the root region of the tongue. In some cases, the metastatic node can be the primary focus.  The most effective complex therapy is surgical intervention with followed radiation therapy in combination with chemotherapy. The spectrum (range) of diagnostic procedures can include bilateral tonsillectomy and mucosectomy of the root region of the tongue.